Transformative? Integrative? Troublesome? Undergraduate Student Reflections on Information Literacy Threshold Concepts - Rachel E. Scott (Communications in Information Literacy, 2017)
In this exploratory study the authors ask students enrolled in a credit-bearing undergraduate research methods course to rank and evaluate the troublesome, transformative, and integrative nature of the six frames currently comprising the Framework for Information Literacy for Higher Education. The results indicate that students have valid insights into threshold concept-based instruction, but may confuse the application with the theory. If practitioners are to embrace not only the frames, but also the spirit of the Framework, we must directly involve students in our teaching and research practices.